2014
DOI: 10.5152/iao.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Post Operative Bone Conduction Hearing after Labyrinthine Fistula Repair in Chronic Otitis Media with Cholesteatoma: A Review of 23 Cases

Abstract: OBJECTIVE:Labyrinthine fistula can lead to hearing loss, dizziness, and intracranial complications. The management of labyrinthine fistula is controversial, and hearing preservation represents a major challenge. In this study, the authors sought to identify factors related to postoperative bone conduction threshold. MATERIALS and METHODS:This retrospective study was conducted using the clinical records of 23 cases operated on for chronic otitis media with cholesteatoma from 2004-2011. Symptoms, physical examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Among 947 patients affected by LF, a slight male prevalence was observed (pooled proportion, 55%; 95% CI, 51–59%; I 2 = 41%). Mean and median ages at diagnosis were quite heterogeneous, reported to be in the fourth decade by 7 studies (17,24,29,32,39,46,47), in the fifth by 9 (7,9,16,23,25,28,38,41,45), and in the sixth by 10 (10,11,26,27,31,33–35,37,43).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 947 patients affected by LF, a slight male prevalence was observed (pooled proportion, 55%; 95% CI, 51–59%; I 2 = 41%). Mean and median ages at diagnosis were quite heterogeneous, reported to be in the fourth decade by 7 studies (17,24,29,32,39,46,47), in the fifth by 9 (7,9,16,23,25,28,38,41,45), and in the sixth by 10 (10,11,26,27,31,33–35,37,43).…”
Section: Resultsmentioning
confidence: 99%
“…Although rather variable, canal wall down (CWD) or radical mastoidectomy were the most common procedures performed in most studies (2,9,10,(16)(17)(18)(24)(25)(26)(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)42,43,47), with a pooled proportion of 88% (95% CI, 79-94%; I 2 = 81%). LFs were most frequently located on the LSCC, with a pooled proportion of 90% (95% CI, 87-93%; I 2 = 46%).…”
Section: Characteristics Of Lfs and Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 28 studies reported hearing data. 2,5-31 One of these articles was excluded because only 1 patient was reported in the study. 31 Of the remaining 27 studies, no significant difference was noted between the matrix removal versus exteriorization (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…All studies that directly compared the 2 were analyzed separately using odds ratios—greater than 1 favored staged matrix removal, and less than 1 favored an unstaged removal. 2,5-7,9-28…”
Section: Methodsmentioning
confidence: 99%